Eosinophilic cytoplasmic inclusions in type 2 papillary renal cell carcinoma - Ungari, M.; Trombatore, M.; Ferrero, G.; Gusolfino, M.D.; Manotti, L.; Tanzi, G.; Varotti, E.; Bertoni, R. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2019)
A case of a patient with type 2 papillary renal cell carcinoma with eosinophilic cytoplasmatic inclusions is presented. About 50% of tumor cells were characterized by a well-circumscribed intra-cytoplasmatic round-to-oval or irregular inclusion/globule. Inclusions were 7-30 micron in diameter. They were glassy and pale to slightly eosinophilic in color in hematoxylin and eosin, were stained red by trichrome and were negative for periodic acid-Schiff reaction. Immunohistochemically, globules were negative for PAX8, epithelial membrane antigen, Carbonic Anhydrase IX, pan-cytokeratin (AE1/AE3), CD10, S100 protein, α-smooth-muscle actin, cytokeratin 7 and cytokeratin 34βE12. Glassy hyaline globules were not detected in any adjacent normal kidney cells. The presence of eosinophilic cytoplasmic inclusions in renal cell carcinoma, especially in papillary renal cell carcinoma, has been rarely emphasized in the literature. In this article, we review similar cases in the literature and discuss the nature of eosinophilic globules.